The Effect of Social Media on the Development of Peaceful Behavior Among High School Youth in Gorontalo Regency - Chaterina Puteri Doni; Sriwahyuningsih R Saleh (Journal La Sociale, 2022)
This study aims to provide an understanding of the influence of social media on the development of peaceful behavior among high school youth in Gorontalo Regency. This research was conducted in ten high schools in Gorontalo Regency, consisting of seven public high schools and three private high schools. Using qualitative research and phenomenological approaches. Respondents in this study were high school students in class XI taken from ten public and private high schools as a representation of the population of high school students in class XI in Gorontalo District High School. The data was obtained by using a questionnaire method which was distributed to 100 respondents regarding the influence of social media on the development of peaceful behavior for high school youth in Gorontalo Regency. The data is then analyzed using the Content Analysis technique to determine the effect of social media on the behavior development of high school youth throughout Gorontalo Regency. The results of this study indicate that adolescents have various concepts of peaceful behavior and one of them is influenced by the media. The concept developed starts from the aspect of how to interact with each other, seen from the effects caused by their behavior, and in terms of the conditions they have. Peaceful behavior among adolescents includes self-directed behavior and behavior directed at others, both protective and promotive. Included in peaceful behavior are all behaviors that individuals themselves feel comfortable with, do not cause problems in society, and behaviors that foster friendship among adolescents.